Assessment of microgrid voltage regulation control methods - Ng, Jun Wei (2018)
Microgrid has become increasingly essential to the modern power system as to ensure local and reliable energy for communities and provide solutions in renewable technology development. The reliability of the microgrid depends on the voltage control and stability of the power system. In island mode, the microgrid faces challenges such as maintaining the voltage levels in range. Therefore, this paper aims to examine the voltage regulation solutions by exploring the proposed methods in literature, namely the Adaptive Droop Control. The conventional droop method facilitates voltage regulation in microgrid but has a trade-off of poor current and load sharing. Adaptive Droop Control method present the methodology of the proposed calculation of minimum droop index to obtain the optimal voltage regulation and power sharing. Furthermore, the concept of shifting of the droop resistance was introduced to improve the load sharing between the converters. This paper will first address the concept and design of the control schemes and subsequent the assessment and analysis of the simulation results which includes the voltage deviation, power and current sharing of the microgrid.